Basic Concepts on the Role of Nuclear Factor Erythroid-Derived 2-Like 2 (Nrf2) in Age-Related Diseases - Francisqueti-Ferron, Fabiane Valentini [UNESP]; Togneri Ferron, Artur Junio [UNESP]; Garcia, Jessica Leite [UNESP]; Vagula de Almeida Silva, Carol Cristina [UNESP]; Costa, Mariane Rovero [UNESP]; Gregolin, Cristina Schmitt [UNESP]; Moreto, Fernando [UNESP]; Ferreira, Ana Lucia A. [UNESP]; Minatel, Igor Otavio [UNESP]; Corrêa, Camila Renata [UNESP] (Mdpi, 2019)
The transcription factor Nrf2 (nuclear factor erythroid 2-related factor 2) is one of the most important oxidative stress regulator in the human body. Once Nrf2 regulates the expression of a large number of cytoprotective genes, it plays a crucial role in the prevention of several diseases, including age-related disorders. However, the involvement of Nrf2 on these conditions is complex and needs to be clarified. Here, a brief compilation of the Nrf2 enrollment in the pathophysiology of the most common age-related diseases and bring insights for future research on the Nrf2 pathway is described. This review shows a controversial response of this transcriptional factor on the presented diseases. This reinforces the necessity of more studies to investigate modulation strategies for Nrf2, making it a possible therapeutic target in the treatment of age-related disorders.
Keywords: Nrf2; age-related disorders; oxidative stress